Revisiting Privatization and Economic Growth in Malaysia: An Empirical Examination - Lai, Fong Woon (2018)

(untitled)
The rapid expansion of the public sector’s investment in the early 1970s and 1980s in Malaysia had resulted in a bloated bureaucracy, inefficiency, high costs and low productivity. The emergence of privatization policy in Malaysia aimed to reduce the financial burden of government, increase the level of efficiency and productivity, increase firm’s revenue, improve the country’s fiscal position and encourage foreign direct investment. Nevertheless, some privatization initiatives are controversial. This paper re- examines the relationship between privatization and economic growth in Malaysia. Two sets of annual macro- economic data from 1984 to 1990 and 2009 to 2015 were used. Descriptive and frequency analysis was used to test the hypothesized relationship between privatization program and its impact on the nation’s macroeconomic benefits namely GDP growth, job creation as well as FDI inflows. By looking at the economic data sets, this paper found that the influence of p